Design and fabricate a droplet formation nozzle for dispersion system - Mohamad Nazreen, Sharan (2013)
The title is building a Droplet Formation Nozzle. The student needs to design and fabricate a Droplet Formation Nozzle for dispersion system. It is to overcome oil pollution problems that happened at sea area. The project started with the flow chart to achieve the objective of this project. Then, the sketching of the design will be selected based on the selection and comparison concept table. Next, it will be design in the Solid Work software. The fabrication process can proceed after the design is finish. In order to finish the project, there are various fabrication processes is needed. All the skill had been taught during previous lab session in UMP. The nozzle had been tested using 3 bar pressure of water and the image of spray from the nozzle was captured and the result based on the picture. This project was referenced from an AFEDO nozzle with some design change to analyze the differences result. This project is done to help in recovering the oil pollution using dispersion system.